2007
DOI: 10.1016/j.str.2006.12.006
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Structural Variation in Computational Models and Crystallographic Data

Abstract: Normal mode analysis offers an efficient way of modeling the conformational flexibility of protein structures. We use anisotropic displacement parameters from crystallography to test the quality of prediction of both the magnitude and directionality of conformational flexibility. Normal modes from four simple elastic network model potentials and from the CHARMM force field are calculated for a data set of 83 diverse, ultrahigh-resolution crystal structures. While all five potentials provide good predictions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 53 publications
8
136
0
Order By: Relevance
“…3-5, 16, 24, 37 It was shown that the GNM is about one order more efficient than most other approaches. 48 Improvements to these approaches have been developed for many aspects, including crystal periodicity and cofactor corrections, 17,21,22,35 and density -cluster rotational -translational blocking. 11 These approaches have been applied to the study of large proteins or protein complexes, such as, hemoglobin, 47 F1 ATPase, 10,50 chaperonin GroEL, 20, 49 viral capsids, 29,36 and ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…3-5, 16, 24, 37 It was shown that the GNM is about one order more efficient than most other approaches. 48 Improvements to these approaches have been developed for many aspects, including crystal periodicity and cofactor corrections, 17,21,22,35 and density -cluster rotational -translational blocking. 11 These approaches have been applied to the study of large proteins or protein complexes, such as, hemoglobin, 47 F1 ATPase, 10,50 chaperonin GroEL, 20, 49 viral capsids, 29,36 and ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…Such lowenergy eigenvalues reflect the long-time behavior of the protein dynamics beyond the reach of MD simulations. 6,8,36,55,58 These approaches have been improved in many aspects including crystal periodicity corrections 28,34,35,54 and densitycluster rotational-translational blocking. 20 These methods are relatively inexpensive particularly in their coarse-grained settings.…”
Section: Introductionmentioning
confidence: 99%
“…The ENM for isotropic fluctuations is called the Gaussian network model (GNM) (23,24), where only the magnitudes of the fluctuations are considered. Its anisotropic counterpart, where the directions of the collective motions are also examined, is called the anisotropic network model (ANM) (25), and these can be compared with the experimental anisotropic temperature factors (26)(27)(28)(29), but generally these comparisons are worse than when atomic representations are used (30).…”
mentioning
confidence: 99%